The relationship between teachers’ emotional intelligence and teaching for creativity: The mediating role of working engagement - Su, Huili; Zhang, Jingwei; Xie, Mingyue; Zhao, Ming (Frontiers in Psychology, 2022)
Teaching for creativity (TfC) has received increasing attention as an important way to cultivate students’ creative thinking and behaviors. This study aims to investigate the mediating role of teachers’ work engagement (WE) on the relationship between their emotional intelligence (EI) and teaching for creativity. The study employed a cross-sectional design. The sample of the study is 3,307 secondary school English teachers working in Jilin Province, China. The findings show that the teachers’ perceptions of emotional intelligence, work engagement and teaching for creativity are relatively high. The findings confirm the hypotheses. The results of structural equation modeling and bootstrapping show that teachers’ emotional intelligence is positively correlated with work engagement and teaching for creativity, and teachers’ work engagement mediates the relationship between emotional intelligence and teaching for creativity.